AN EXPLORATORY STUDY ON THE CULTURAL BARRIERS IMPACTING WOMEN ENTREPRENEURSHIP IN THE HOSPITALITY INDUSTRY IN INDIA (PUSA Journal of Hospitality and Applied Sciences, 2024)
Background: Entrepreneurship is a complex, multidimensional phenomenon that involves value creation and considered  as a driving force of economic development. Entrepreneurship is one of the growing trends, and studies are focusing  on it generally not only at the national but also at the global level. Objectives: To explore the cultural barriers in  various Indian communities that limits the movement of women towards entrepreneurship in the hospitality business  and suggest ways to overcome such barriers for women development. Methodology: The research design of the study  was both qualitative and quantitative. The present study was conducted in Kolkata. The sample was collected from 43  female entrepreneur associated with various hotel oriented business using the convenience sampling technique. A well structured questionnaire was used to collect the data. Results: The study found that 32.6% of the female entrepreneurs  faced financial issue as one of the biggest challenge. It was also found that 44.2% of women did not have the freedom  to market the product. 25.6% of the women entrepreneurs mentioned that family commitment always affected the  business performance. 44.2% of women were of the opinion that they faced psychological challenges in dealing with  men in the hospitality sector. Majority of women (around 51.2%) faced problems in availing the facility of government  funds whereas around (50.5%) faced challenges in loan sanctions. Conclusion: It was found that family and societal  commitments and domination of men in the society in terms of business were key factors to the hindrances Support from  the government and formulation of policies can be a matter of great help in this regard.
Keywords: Women Entrepreneurship; Indian Culture; Cultural Barriers; Hospitality Industry